Stability assessment of a high speed permanent magnet machine based aircraft electrical power system - Gao, Fei; Yeoh, Seang Shen; Hill, Christopher Ian; Yang, Tao; Bozhko, Serhiy (2016)
Starting an aircraft engine with an electrical machine has been one of the major trends for future aircraft. This paper studies the stability of a permanent-magnet machine (PMM) based aircraft starter/generator (S/G) system. Using control-to-output transfer functions, the stability analysis of this S/G system is thoroughly studied. The impact of the key parameters including the control parameters is analysed. Simulation and experimental results support the analytical result.